Exploration of Textual Criticism on The Fiqh Ulakan Manuscript: A Study of Philological Analysis, Scribal Errors, Uniqueness, and Historical Context - Nurul 'Afifah; Soraya, Lusi; Hafsoh, Yen Leli (Titian: Jurnal Ilmu Humaniora, 2024)
his article is a philological study of the Fiqih Manuscript from Ulakan, Pariaman, West Sumatera. This manuscript discusses various aspects of fiqih, such as the obligatory bath and its conditions, the conditions for water used in ablution, the requirements for valid prayers, etc. The aim of this study is to perform a textual criticism of the Ulakan fiqih manuscript and to analyze its content. To achieve this purpose, this study employs philological methods. The results show errors in the fiqih manuscript in the form of substitutions, additions, and omissions. The most common errors were found in additions. Most of the errors occurred at the letter level and did not significantly affect the contextual understanding of the manuscript, nor did they substantially impact the readers' comprehension, as these errors were not critical. After conducting a literature review and exploring several manuscripts, it can be concluded that the Ulakan Fiqih Manuscript belongs to the Syattariyah Order and is used for religious education. Abstract Artikel ini merupakan kajian filologi terhadap Naskah Fiqih dari Ulakan, Pariaman, Sumatera Barat. Naskah ini membahas berbagai aspek fiqih, seperti mandi wajib dan syaratnya, syarat-syarat air untuk wudhu, syarat sah shalat, dan sebagainya. Penelitian ini bertujuan untuk melakukan kritik teks terhadap naskah kitab fiqih Ulakan serta menganalisis isi teksnya. Untuk mencapai tujuan tersebut, penelitian ini menggunakan metode filologi. Hasil penelitian menunjukkan adanya kesalahan dalam naskah kitab fiqih, berupa substitusi, adisi, dan omisi. Kesalahan terbanyak ditemukan dalam kasus adisi. Kesalahan tulis yang terjadi kebanyakan berada pada tataran huruf saja, dan kesalahan ini tidak begitu memengaruhi pemahaman kontekstual terhadap naskah, dan tidak terlalu mempengaruhi pemahaman pembaca, karena kesalahan-kesalahan tersebut tidak terlalu krusial. Setelah dilakukan studi literatur dan eksplorasi terhadap beberapa naskah, dapat disimpulkan bahwa Naskah Fiqih Ulakan merupakan milik Tarekat Syattariyah dan digunakan untuk pengajaran agama.